211k views
5 votes
X + y = 26
3x + y = 56

Please help me! Show Working Please

User Elise
by
4.6k points

2 Answers

1 vote

Explanation:

(X + y = 26) (-3)

3x + y = 56

____________

- 3 x - 3y = - 78 Note:cross 3x and-3x from both equations (they're opposite)

3x +y =56

____________

-3y +y = - 78 +56

-2y = - 22


y = ( - 22)/( - 2) = 11

____________

So we replace y in eq 2: (to obtain x)

3x + 11 =56

3x =45

X =15

User Tskuzzy
by
5.2k points
4 votes

Answer:

x = 15

y = 11

Explanation:

15+11=26

(3*15)+11=56

User Kiheru
by
5.3k points